“No somos estadísticas “- la prueba rapida del VIH y la consejería de los representantes de las personas LGBT (2019)
This study was aim to analyze how representatives of LGBT NGOs perceive strategies about the inclusion of the rapid test for HIV/aids, syphilis and viral hepatitis in the LGBT scenario of Porto Alegre. It is a qualitative study in which 4 representatives were interviewed, and the interviews were analyzed through a critical analysis of discourse. The results point to a concern of the interviewees with the care strategies that are built with the test and how much they dialogue with human rights. This leads to tensions that have as a background the relations between State, LGBT movements and HIV. Ignoring political issues that permeate these relations depoliticizes a history in which the greatest advances in terms of prevention and confrontation have gone through a united response between different social actors. Building new spaces for discussion can allow new collective strategies to be considered in coping with the epidemic, prejudice and stigma.